ENHANCING SELF-DIRECTED LEARNING IN ARABIC SPEAKING COMPETENCY THROUGH DORATOON AND GOOGLE SITES - Nurul Hidayah; Mukmin Mukmin; Nabila Nurul Aini; Febri Yansyah; Nur Khamimi Zainuddin (Thariqah Ilmiah: Jurnal ilmu-ilmu kependidikan & Bahasa Arab, 2026)
One of the main challenges in teaching maharah kalam, or Arabic speaking skills, is the lack of real opportunities for meaningful oral interaction. Traditional, teacher-centred methods are still widely used, which often limits students’ ability to communicate confidently and independently. This study set out to explore how integrating Self-Directed Learning (SDL) with digital tools like Doratoon and Google Sites could help overcome these challenges. Using a combination of qualitative and quantitative approaches, the research gathered insights from classroom observations, interviews, and documentation, as well as pre- and post-tests involving 30 students. The results showed a noticeable shift from teacher-led instruction to a more student-centred and participative environment. Students’ average speaking scores improved significantly, rising from 57.33 to 91.33, with an N-Gain of 80.56%. These findings suggest that when technology is thoughtfully combined with SDL, it can create a more engaging, autonomous, and effective learning experience for students. Ultimately, this study offers a promising new model for making Arabic-speaking instruction more dynamic and centred on the learner.